Análisis del divorcio incausado para instituirlo en el código civil, como forma determinación del matrimonio, ante la dificultad de ejercitar prueba en el divorcio por causales. - Viteri Ordoñez, Bryan Enrique (2024)
This study, titled "Analysis of no-fault divorce to incorporate it into the civil code as a means of terminating marriage, in light of the difficulty of providing evidence in fault-based divorce," presents a profound reflection on current matrimonial legislation. Article 110 of the Ecuadorian Civil Code establishes provisions related to divorce, but the requirement of specific evidence for fault-based divorce can create difficulties in its practical application. The objective of this research is to explore the feasibility and implications of introducing no-fault divorce into the Ecuadorian legal framework as an alternative to fault-based divorce. This measure aims to facilitate the dissolution of marriage in cases where the burden of proof is complicated or impossible to satisfy. In this context, a thorough analysis of relevant legal provisions is necessary, as well as of constitutional principles that guarantee rights such as personal and family privacy, the free development of personality, and the psychological integrity of indirectly involved priority groups. It is proposed to examine the experience of other countries that have implemented no-fault divorce, as well as the opinions of experts in family law and related jurisprudence. For the relevant development of this work, various research parameters have been established, such as legal, conceptual, and doctrinal. The type of research conducted was legal and doctrinal, and various necessary methods were used, such as inductive, deductive, analytical, exegetical, Socratic, comparative, statistical, and synthetic.